AMBER: A Device for Hand Motor and Cognitive Rehabilitation—Development and Proof of Concept - Laura Valenzuela-Lopez; Marcos Moreno-Verdu; Roberto Alvarez; Gabriel Delgado-Oleas; Luis Soliverdi Mesa; Aida Arroyo-Ferrer; Francisco Jose Sanchez-Cuesta; Yeray Gonzalez-Zamorano; Mercedes Barrachina Fernandez; Carmen Sanchez Avila; Juan Pablo Romero (IEEE, 2024)
Stroke survivors usually exhibit concurrent motor and cognitive impairment. Historically, rehabilitation strategies post-stroke occur separately in terms of motor and cognitive functions. However, recent studies show that hand motor interventions can have a positive impact on cognitive recovery. In this work, we introduce AMBER (portAble and Modular device for comprehensive Brain Evaluation and Rehabilitation), a new device developed for the evaluation and rehabilitation of both hand motor function and cognition simultaneously. AMBER is a simple, portable, ergonomic and cheap device based on Force Sensitive Resistors, in which every finger interaction is recorded to provide information about finger strength, processing speed, and memory status. This paper presents the requirements of the device and the design of the system. In addition, a pilot study was conducted with 36 healthy individuals using the evaluation module of the device to assess its psychometric properties, as test-retest reliability and measurement error. Its validity was also evaluated comparing its measurements with three different gold standards for strength, processing speed and memory. The device showed good test-retest reliability for strength (ICC =0.741-0.852), reaction time (ICC =0.715 – 0.900) and memory (ICC =0.556-0.885). These measures were correlated with their corresponding gold standards (r =0.780-890). AMBER shows great potential to impact hand rehabilitation, offering therapists a valid, reliable and versatile tool to comprehensively assess patients. With ongoing advancements and refinements, it has the opportunity to significantly impact rehabilitation practices and improve patient outcomes.